DERIVATIONAL AFFIXES IN MANADO-MALAY AND ENGLISH LANGUAGES (A CONTRASTIVE ANALYSIS) - Angelita Sumenge; Maikel Sanger; Yapi Wongkar (Program Studi Pendidikan Bahasa Inggris, 2023)
This research aims to describe and analyse the derivational affixes of both Manado-Malay and English languages in term of form and meaning in verb, adjective, noun and adverb, and the similarities and differences of derivational affixes in Manado-Malay and English languages by using O’Grady’s (1987) theory and contrasting them using Lado’s (1971) method. The English data were collected from several sources: English book, such Contemporary Linguistic Analysis: An Introduction by O’Grady/ Dobrovolsky, English Dictionary and looking for some information from internet media related to derivation affixes in English and Manado-Malay data were taken from three native speaker as informants who were born and lived in the land of Manado. The result of this research showed that the types of English derivational affixes are prefixes and suffixes. The types of Manado-Malay derivational affixes are prefixes, suffixes, and confixes. The function of both English and Manado-Malay derivational affixes are to create new lexeme that may change the parts of speech or not. The similarities between Manado-Malay and English are that both languages have prefixes and suffixes process. The differences of both derivational affixes are English derivational affixes form new English words through prefixation and suffixation; meanwhile, there are confixation in Manado-Malay language. Noun-forming prefixes in English are only attached to noun bases, while in Manado-Malay noun-forming prefixes can be attached to the base of noun, verbs and adjectives. Suffix forms in English form nouns, verbs, adjectives and adverbs.